2022
DOI: 10.5194/isprs-annals-v-4-2022-99-2022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Massive Imports of Open Data in Openstreetmap Database: A Study Case for France

Abstract: Abstract. Importing spatial open data in OpenStreetMap (OSM) project, is a practice that has existed from the beginning of the project. The rapid development and multiplication of collaborative mapping tools and open data have led to the growth of the phenomenon of importing massive data into OSM. The goal of this paper is to study the evolution of the massive imports over time. We propose an approach in three steps: classification of the sources used to edit features in the OSM platform including those massiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(24 reference statements)
1
0
0
Order By: Relevance
“…However, Paiva and Camboim (2021) demonstrated that this approach alone would not explain the entire behaviour of quality in VGI. Such aspect converges with research recently conducted aimed at detailing temporal patterns and thereby improving the understanding of the spatial distribution of its quality (Le Guilcher, Olteanu-Raimond and Balde, 2022;Grinberger et al, 2021;Brückner et al, 2021;Witt, Loos and Zipf 2021;Arsanjani et al 2015;Gröching, Brunauer and Rehr 2014).…”
Section: Introductionsupporting
confidence: 67%
“…However, Paiva and Camboim (2021) demonstrated that this approach alone would not explain the entire behaviour of quality in VGI. Such aspect converges with research recently conducted aimed at detailing temporal patterns and thereby improving the understanding of the spatial distribution of its quality (Le Guilcher, Olteanu-Raimond and Balde, 2022;Grinberger et al, 2021;Brückner et al, 2021;Witt, Loos and Zipf 2021;Arsanjani et al 2015;Gröching, Brunauer and Rehr 2014).…”
Section: Introductionsupporting
confidence: 67%